2017
DOI: 10.3144/expresspolymlett.2017.35
|View full text |Cite
|
Sign up to set email alerts
|

Role of nanosilica localization on morphology development of HDPE/PS/PMMA immiscible ternary blends

Abstract: Abstract. In this work, we studied the parameters affecting the localization of hydrophobic nanosilica particles and its impact on morphology development of polyethylene/polystyrene/poly (methyl methacrylate) (HDPE/PS/PMMA) ternary blends, which originally have a thermodynamically preferred core-shell type morphology, by means of a combination of rheology and electron microscopy. An attempt was also made to compare the experimental results with thermodynamic predictions. The ternary blend samples with the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…This gel-like behavior of TPS has been shown to be originated from the single helix crystalline regions and the physical entanglement of highmolecular weight polysaccharide molecules. [28][29][30][31][32][33][34] Della Valle et al reported significant differences in the rheological behavior of TPS samples with different botanical origins, which could be attributed to their molecular-scale features such as chain length and linearity, favoring the entanglement of the amorphous phase rather than strengthening the crystalline structure. [28] Gonzalez et al suggested that the variation of glycerol content did not affect the contribution of single-helix crystallinity to strengthening of elastic network of TPS, but rather merely plasticized the amorphous fraction of starch.…”
Section: Introductionmentioning
confidence: 99%
“…This gel-like behavior of TPS has been shown to be originated from the single helix crystalline regions and the physical entanglement of highmolecular weight polysaccharide molecules. [28][29][30][31][32][33][34] Della Valle et al reported significant differences in the rheological behavior of TPS samples with different botanical origins, which could be attributed to their molecular-scale features such as chain length and linearity, favoring the entanglement of the amorphous phase rather than strengthening the crystalline structure. [28] Gonzalez et al suggested that the variation of glycerol content did not affect the contribution of single-helix crystallinity to strengthening of elastic network of TPS, but rather merely plasticized the amorphous fraction of starch.…”
Section: Introductionmentioning
confidence: 99%
“…In the experimental study, molecular dynamics simulation (MDS) and theoretical analysis show that the actual volume flow in nanopores can be increased by 1-5 times of magnitude compared with the volume flow predicted by the nonslip Hagen-Poiseuille equation [30]. The enhanced flowability of fluid is caused by boundary slip, and it is affected by a variety of physical means, including solid-liquid molecular interaction force [31], wall roughness [32], shear rate [33], nanobubbles [34], fluid polarity [35], fluid viscosity [36], pore size [37], and pressure gradient [38].…”
Section: Single Phase Migration Mechanism In Shalementioning
confidence: 99%
“…In this work, the Guggenheim equation is adopted to describe relationship between surface tension and temperature [69] where 0 is a temperature-independent constant (surface tension of water with temperature equaling to 0 K), stands for reduced temperature which can be de ned as the ratio of temperature to the critical temperature = / , is the critical temperature, and = 647.3 K for water. e temperature gradient of the surface tension for liquid is shown below [12] (14) = 1 + cos 0 2 .…”
Section: Work Of Adhesion In the Previous Work Mattia Andmentioning
confidence: 99%
“…e results, measured or calculated by experimental studies, Molecular Dynamics Simulations (MDS), and theoretical studies, have shown that the enhanced water ow capacity in nanopores can be up to 1-5 orders of magnitude compared to that predicted by the no-slip Hagen-Poiseuille (HP) equation [4][5][6]. e behaviors of enhanced water ow are related to the boundary slip depending on many physical mechanisms, including pore wall-water molecular interactions (that can be expressed by surface wettability or contact angle) [7,8], pore wall roughness [9][10][11][12], shear rate [13,14], nanobubbles or gas lms [15,16], polarity of liquids [15][16][17][18], water viscosity [19,20], temperature [21], pore dimensions [22], and pressure gradient [23]. In general, the boundary slip length is usually obtained by two methods: (1) microscopic slip length is observed by MDS; (2) macroscopic slip length is measured by experiments, and that cannot quantify the e ect of each physical mechanism [1,24].…”
Section: Introductionmentioning
confidence: 99%